Pockets of HIV Non-infection Within Highly-Infected Risk Networks in Athens, Greece - Williams, Leslie D.; Kostaki, Evangelia-Georgia; Pavlitina, Eirini; Paraskevis, Dimitrios; Hatzakis, Angelos; Schneider, John; Smyrnov, Pavlo; Hadjikou, Andria; Nikolopoulos, Georgios K.; Psichogiou, Mina; Friedman, Samuel R. (Frontiers in Microbiology, 2018)
As part of a network study of HIV infection among people who inject drugs (PWID) and their contacts, we discovered a connected subcomponent of 29 PWID. In the context of a just-declining large epidemic outbreak, this raised a question: What explains the existence of large pockets of uninfected people? Possible explanations include “firewall effects” (Friedman et al 2001; Dombrowski et al 2017) wherein the only HIV+ people they take risks with have low viral loads; “bottleneck effects” wherein few network paths into the pocket of non-infection exist; low risk behaviors; and an impending outbreak. We tested each of these. Participants provided information on their enhanced sexual and injection networks and assisted us in recruiting network members. The largest connected component had 92 members. Data on risk behaviors in the last 6 months were collected at the individual level. Recent infection was determined by LAg (SediaTM Biosciences Corporation), data on recent seronegative tests, and viral load. HIV-RNA was quantified using Artus HI Virus-1 RG RT-PCR (Qiagen). The 29 members of the connected subcomponent of uninfected participants were connected (network distance = 1) to 17 recently-infected and 24 long-term infected participants. Fourteen (48%) of these 29 uninfected were classified as “extremely high risk” because they self-reported syringe sharing and had at least one injection partner with viral load > 100,000 copies/mL. Seventeen of the 29 uninfected were re-interviewed after six months, but none had seroconverted. These findings show the power of network research in discovering infection patterns that standard individual-level studies cannot. Theoretical development and exploratory network research studies may be needed to understand these findings and deepen our understanding of how HIV does and does not spread through communities. Finally, the methods developed here provide practical tools to study “bottleneck” and “firewall” network hypotheses in practice.